Aviation maintenance management - Kinnison, Harry A. (McGraw Hill, 2004)
This unique resource covers aircraft maintenance program development and operations from a managerial as well as technical perspective. Readers will learn how to save money by minimizing aircraft downtime and slashing maintenance and repair costs.